Synthetic Assembly DNA Cloning to Build Plasmids for Multiplexed Transgenic Selection, Counterselection or Any Other Genetic Strategies Using Drosophila melanogaster. Issue 2 (9th February 2023) - Venken, Koen J. T.; Matinyan, Nick; Gonzalez, Yezabel; Sarrion‐Perdigones, Alejandro; Dierick, Herman A.
Abstract: We recently described a drug‐based selectable and counterselectable genetic platform for the animal model system Drosophila melanogaster, consisting of four resistance and two sensitivity markers that allow direct selection for, or counterselection against, a desired genotype. This platform eliminates the need to identify modified progeny by traditional laborious screening using the dominant eye and body color markers, white + and yellow +, respectively. The four resistance markers permit selection of animals using G418 sulfate, puromycin HCl, blasticidin S, or hygromycin B, while the two sensitivity markers allow counterselection of animals against ganciclovir or acyclovir and 5‐fluorocytosine. The six markers can be used alone or in combination to perform co‐selection, combination selection, and counterselection, as well as co‐counterselection. To make this novel selection and counterselection genetics platform easily accessible to and rapidly implementable by the scientific community, we used a synthetic assembly DNA cloning platform, GoldenBraid 2.0 (GB2.0). GB2.0 relies on two Type IIs restriction enzymes that are alternatingly used during successive cloning steps to make increasingly complex genetic constructs. Here we describe, as an example, how to perform synthetic assembly DNA cloning using GB2.0 to build such complex plasmids via the assembly of both components of the binary LexA/ LexA‐Op overexpression system, a G418 sulfate–selectable LexA transactivator plasmid, and a blasticidin S–selectable LexA‐Op responder plasmid. We demonstrate the functionality of these plasmids by including the expression pattern obtained after co‐injection, followed by co‐selection using G418 sulfate and blasticidin S, resulting in co‐transgenesis of both plasmids. Protocols are provided on how to obtain, adapt, and clone DNA parts for synthetic assembly cloning after de novo DNA synthesis or PCR amplification of desired DNA parts and how to assemble those DNA parts into multipartite transcription units, followed by how to further assemble multiple transcription units into genetic constructs of increasing complexity to perform multiplexed transgenic selection and counterselection, or any other genetic strategies using Drosophila melanogaster . The protocols we present can be easily adapted to incorporate any of the six selectable and counterselectable markers, or any other, markers, to generate plasmids of unmatched complexity for various genetic applications. A protocol on how to generate transgenic animals using these synthetically assembled plasmids is described in an accompanying Current Protocols article (Venken, Matinyan, Gonzalez, & Dierick, 2023). © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Obtaining and cloning a de novo –synthesized DNA part for synthetic assembly DNA cloning Basic Protocol 2 : Obtaining and cloning a DNA part amplified by PCR from existing DNA resources for synthetic assembly DNA cloning Alternate Protocol : Obtaining, adapting, and cloning a DNA part amplified by PCR from existing DNA resources for synthetic assembly DNA cloning Basic Protocol 3 : Synthetic assembly DNA cloning of individual DNA parts into a multipartite transcription unit Basic Protocol 4 : Synthetic assembly DNA cloning of multiple transcription units into genetic constructs of increasing complexity